Study Abroad Connecting Across Topics (CAT) Community 2013 - Kansas State University, K-State First (Kansas State University. K-State First., 2013)
A brochure describing Study Abroad Connecting Across Topics (CAT) Communities at Kansas State University for the 2015-2016. Provided in the brochure is a description of the community, available scholarships, and a brief overview of how CAT Communities operate.
Keywords: Guide; CAT communities; First-year experience program; Study Abroad; Fliers (printed matter)